Intra-arterial idarubicin_lipiodol without embolization can provide prolonged complete response in hepatocellular carcinoma: A case report. (March 2020) - Pistre, Pauline; Guiu, Boris; Gehin, Sophie; Boulin, Mathieu
Hepatocellular carcinoma is the fourth leading cause of cancer death. For unresectable intermediate-stage hepatocellular carcinoma, the standard treatment is transarterial chemoembolization. To date, the overall survival at three years remains low, and there is currently no consensus about the best anticancer agent and optimal treatment regimen. We report the case of a hepatocellular carcinoma patient with a vascular contraindication to embolization who achieved a complete response after four intra-arterial infusions of idarubicin emulsified with lipiodol. The patient maintained his response over a three-year period without any hepatocellular carcinoma treatment, demonstrating the major role of the anticancer agent in the efficacy of transarterial therapies for intermediate-stage hepatocellular carcinoma.